A Rare Case of Juvenile Idiopathic Arthritis following a Ruptured Baker's Cyst in a Toddler. (6th April 2020) - Üstüner, Deniz; Asaid, Fatma; Pervaiz, Muhammad; Oligbu, Godwin
Abstract : A Baker's cyst is usually an incidental finding in adults being investigated for a joint arthropathy, and its rupture preceding the diagnosis of juvenile idiopathic arthritis (JIA) is rare in children. Here, we describe a case of a 4-year-old girl who presented to the Emergency Department with right calf pain, swelling, and no preceding history of trauma. MRI confirmed a ruptured Baker's cyst with inflammatory arthropathy alongside an extensive synovial proliferation throughout the knee joint with large joint effusions and associated soft tissue oedema tracking superiorly and inferiorly along the medial head of gastrocnemius and anteriorly along the tibia. Further investigations revealed bilateral uveitis consistent with a diagnosis of juvenile idiopathic arthritis.